2011
DOI: 10.1001/archoto.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

Local Steroid Injection via the Cricothyroid Membrane in Patients With a Vocal Nodule

Abstract: A local steroid injection via the cricothyroid membrane is a useful and safe treatment option for vocal nodules. However, vocal nodules are caused mainly by excessive voice use; therefore, nodules can recur unless the voice use pattern changes. Further study of this treatment technique, including long-term follow-up, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 25 publications
4
74
1
Order By: Relevance
“…A previous study observed a 5% incidence rate of vocal fold atrophy after VFSI. 36 In contrast, this study revealed a much lower incidence rate (only one of 126 cases). One reasonable explanation for this discrepancy is the different injection approaches.…”
Section: Chi-te Wang Et Alcontrasting
confidence: 74%
See 2 more Smart Citations
“…A previous study observed a 5% incidence rate of vocal fold atrophy after VFSI. 36 In contrast, this study revealed a much lower incidence rate (only one of 126 cases). One reasonable explanation for this discrepancy is the different injection approaches.…”
Section: Chi-te Wang Et Alcontrasting
confidence: 74%
“…For vocal nodules, we demonstrated that VFSI can result in significant subjective and objective improvements ( Table 1, left column), which was comparable with previously published results. 11,36 Moreover, we investigated the prognostic factors of vocal nodules after VFSI, which had not previously been done. The study results demonstrated that patients with higher vocal demand were more likely to perceive higher phonation discomforts as measured by their postoperative VHI-10 scores ( Table 2, upper half).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the treatment of vocal fold scar remains suboptimal. The one exception may be localized steroid injections, which have been reported to show modest, unreliable success in limited case series . We posit that an ideal therapy for vocal fold fibrosis must have targeted and predictable control of both the inflammatory and subsequent fibroplastic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…ISI for VF nodules has been reported in retrospective and prospective case series. Complete resolution rates range between 31% to 44%, with partial regression of 49% to 69% . Whereas most patients demonstrated lesion response to treatment within 1 month, some patients improve only after 3 treatments .…”
Section: Methodsmentioning
confidence: 99%